RET/PTC and PAX8/PPARγ chromosomal rearrangements in post‐Chernobyl thyroid cancer and their association with iodine‐131 radiation dose and other characteristics1. Issue 10 (21st February 2013) - Leeman‐Neill, Rebecca J.; Brenner, Alina V.; Little, Mark P.; Bogdanova, Tetiana I.; Hatch, Maureen; Zurnadzy, Liudmyla Y.; Mabuchi, Kiyohiko; Tronko, Mykola D.; Nikiforov, Yuri E.
Abstract: BACKGROUND: Childhood exposure to iodine‐131 from the 1986 nuclear accident in Chernobyl, Ukraine, led to a sharp increase in papillary thyroid carcinoma (PTC) incidence in regions surrounding the reactor. Data concerning the association between genetic mutations in PTCs and individual radiation doses are limited. METHODS: Mutational analysis was performed on 62 PTCs diagnosed in a Ukrainian cohort of patients who were < 18 years old in 1986 and received 0.008 to 8.6 Gy of 131 I to the thyroid. Associations between mutation types and 131 I dose and other characteristics were explored. RESULTS: RET/PTC (ret proto‐oncogene/papillary thyroid carcinoma) rearrangements were most common (35%), followed by BRAF (15%) and RAS (8%) point mutations. Two tumors carrying PAX8/PPAR γ (paired box 8/peroxisome proliferator‐activated receptor gamma) rearrangement were identified. A significant negative association with 131 I dose for BRAF and RAS point mutations and a significant concave association with 131 I dose, with an inflection point at 1.6 Gy and odds ratio of 2.1, based on a linear‐quadratic model for RET/PTC and PAX8/PPAR γ rearrangements were found. The trends with dose were significantly different between tumors with point mutations and rearrangements. Compared with point mutations, rearrangements were associated with residence in the relatively iodine‐deficient Zhytomyr region, younger age at exposure or surgery, and male sex. CONCLUSIONS: These results provide the first demonstration of PAX8/PPAR γ rearrangements in post‐Chernobyl tumors and show different associations for point mutations and chromosomal rearrangements with 131 I dose and other factors. These data support the relationship between chromosomal rearrangements, but not point mutations, and 131 I exposure and point to a possible role of iodine deficiency in generation of RET/PTC rearrangements in these patients. Cancer 2013. © 2013 American Cancer Society. Abstract : This study of papillary thyroid carcinomas in populations exposed to the 1986 accident in Chernobyl, Ukraine, provides the first documentation of PAX8/PPAR γ rearrangements in post‐Chernobyl thyroid cancer; demonstrates a link between chromosomal rearrangements, but not point mutations, and individual iodine‐131 dose received; and points to a possible role of iodine deficiency in generation of RET/PTC rearrangements in these patients.